Gold‐Catalyzed Intermolecular Anti‐Markovnikov Hydroamination of Alkylidenecyclopropanes1. (22nd December 2014) - Timmerman, Jacob C.; Robertson, Bradley D.; Widenhoefer, Ross A.
Abstract The cationic gold phosphine complex [PCy2(o‐biphenyl)Au(NCMe)]+SbF6− (Cy=cyclohexyl) catalyzes the intermolecular, anti‐Markovnikov hydroamination reaction of monosubstituted and cis‐ and trans‐disubstituted alkylidenecyclopropanes (ACPs) with imidazolidin‐2‐ones and other nucleophiles. This reaction forms 1‐cyclopropyl alkylamine derivatives in high yield and with high regio‐ and diastereoselectivity. NMR spectroscopic analysis of gold π‐ACP complexes and control experiments point to the sp hybridization of the ACP internal alkene carbon atom as controlling the regiochemistry of the ACP hydroamination reaction.